Variation in the Geographic Distribution of the Otolaryngology Workforce: A National Geospatial Analysis - Gadkaree, Shekhar K; McCarty, Justin C; Siu, Jennifer; Shaye, David A; Deschler, Daniel G; Varvares, Mark A; Jarman, Molly; Bergmark, Regan (Otolaryngology-head and neck surgery, 2020)
To examine the current geographic distribution of otolaryngologists in the United States and the disparities in socioeconomic demographics at the county and hospital referral region (HRR) level. Cross-sectional study. National cohort analysis including all otolaryngologists in the United States. All otolaryngologists board certified by the American Board of Otolaryngology-Head and Neck Surgery in the United States in 2018 were compared with overlaid demographic data from the 2010 United States Census Bureau by county and HRR. Associations between the density of otolaryngologists per population and socioeconomic characteristics were assessed and stratified by region. The average number of otolaryngologists was 3.6 (SD 9.6) per 100,000. On multivariable regression analysis, the density of otolaryngologists was positively associated with counties with the highest quartile of college education (1.8 providers per 100,000 [95% confidence interval [CI] 0.89, 2.90], < .001) and income (2.1 providers per 100,000 [95% CI 1.03, 3.07], = .01). Significant regional variation existed in access to otolaryngology care. There are significant areas with disparate densities of otolaryngologists in the United States. Lower socioeconomic status, more severe poverty, and a lower number of college graduates in a county correlated with reduced density of otolaryngologists.